Efficacy and safety of different systemic drugs in the treatment of uremic pruritus among hemodialysis patients: a network meta-analysis based on randomized clinical trials - Zhao, Xueqian; Sun, Haipeng; Li, Wei (Frontiers in Medicine, 2024)
Aim: This network meta-analysis was to analyze and rank the efficacy and safety of different systemic drugs in the treatment of uremic pruritus (UP) among hemodialysis patients.Methods: PubMed, Embase, Cochrane Library, and Web of Science databases were searched from inception to 10 July 2023 for randomized controlled trials (RCTs) investigating different drugs in the treatment of UP among hemodialysis patients. Drugs including cromolyn sodium, dexchlorpheniramine, difelikefalin, gabapentin, hydroxyzine, ketotifen, melatonin, montelukast, nalbuphine, nalfurafine, nemolizumab, nicotinamide, pregabalin, sertraline, thalidomide, and placebo were assessed. Outcome measures including pruritus relief, response, and adverse events were analyzed.Network plots, forest plots, league tables and the surface under the cumulative ranking (SUCRA) probabilities were depicted for each outcome.The network meta-analysis retrieved 22 RCTs. Gabapentin (69.74%) had the highest likelihood to be the most effective drug for pruritus relief in UP patients receiving hemodialysis, followed by cromolyn sodium, and hydroxyzine. Thalidomide (60.69%) and gabapentin (58.99%) were associated with significantly more drug response for treating UP among patients receiving hemodialysis. Patients who were treated with gabapentin (40.01%) were likely to have risks of adverse events and dizziness. Lower risks of adverse events, nausea, and diarrhea were found in patients who received cromolyn sodium and lower risks of somnolence.This study suggested to consider gabapentin treatment when facing a Systemic drugs in the treatment of uremic pruritus among hemodialysis patients 3 patient suffering from UP. This study provides a reference for the selection of drug 39 therapy for UP patients receiving hemodialysis.